Effects of Lycopene Supplementation on Bone Tissue: A Systematic Review of Clinical and Preclinical Evidence - Silva, Arles Naisa Amaral [UNESP]; Nunes, Gabriel Pereira; de Paula Domingues, Danilo Vinicius Aparecido; De Toledo, Priscila Toninatto Alves; Akinsomisoye, Olumide Stephen [UNESP]; Florencio-Silva, Rinaldo; Cerri, Paulo Sérgio [UNESP] (MDPI, 2025)
Background: Bone tissue undergoes continuous remodeling, and imbalances in this process can lead to osteometabolic disorders, such as osteoporosis. Thus, bioactive compounds, like lycopene (LYC), have been investigated for their potential protective effects in bone health. This systematic review (SR) aimed to evaluate the effects of LYC supplementation on bone tissue. Methods: The SR was registered in PROSPERO (CRD42023417346) and followed the PRISMA guidelines. A comprehensive search was conducted in electronic databases up to May 2025. Two independent reviewers selected clinical trials and animal studies evaluating the effects of LYC supplementation in bone tissue. Methodological quality and risk of bias were assessed using the Cochrane Risk of Bias tool for randomized controlled trials, the Newcastle-Ottawa Scale for non-randomized clinical studies, and the SYRCLE tool for animal studies. Results: A total of 21 studies met the eligibility criteria, consisting of 6 clinical trials and 15 studies in animal models. LYC supplementation promotes an increase in bone mineral density, preserves trabecular microarchitecture, stimulates osteoblastic activity, and inhibits osteoblast apoptosis. Conclusions: LYC supplementation promotes beneficial effects on both the formation and preservation of bone tissue, suggesting that this carotenoid may represent a potential adjuvant strategy in the management of osteometabolic disorders.